Alkylphenyl Substituted Naphthodithiophene: A New Building Unit with Conjugated Side Chains for Semiconducting Materials. Issue 21 (23rd September 2014) - Shi, Shaowei; Shi, Keli; Qu, Rui; Mao, Zupan; Wang, Hanlin; Yu, Gui; Li, Xiaoyu; Li, Yongfang; Wang, Haiqiao
<x xml:space="preserve">Abstract</x> In this article, a versatile 2‐D conjugated polymer, PNDTP‐DPP, containing alkylphenyl substituted naphthodithiophene is synthesized and characterized. PNDTP‐DPP exhibits good solubility and crystallinity with a π−π stacking distance of ≈3.7 Å. Investigation of polymer solar cells (PSCs) and organic field‐effect transistors (OFET) demonstrates a promising power conversion efficiency (PCE) of 4.11% and a high hole mobility of up to 0.86 cm2 V–1 s–1, so this is one of the few examples of versatile polymers that show both good field‐effect mobility and PCE. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>